Effect of economic parameters on power generation expansion planning - Sevilgen, SH; Erdem, HH; Cetin, B; Akkaya, AV; Dagdas, A (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The increasing consumption of electricity within time forces countries to build additional power plants. Because of technical and economic differences of the additional power plants, economic methodologies are used to determine the best technology for the additional capacity. The annual levelized cost method is used for this purpose, and the technology giving the minimum value for the additional load range is chosen. However, the economic parameters such as interest rate, construction escalation, fuel escalation, maintenance escalation and discount factor can affect the annual levelized. cost considerably and change the economic range of the plants. Determining the values of the economical parameters in the future is very difficult, especially in developing countries. For this reason, the analysis of the changing rates of the mentioned values is of great importance for the planners of the additional capacity. In this study, the changing rates of the economic parameters that influence the annual levelized. cost of the alternative power plant types are discussed. The alternative power plants considered for the electricity generation sector of Turkey and the economic parameters dominating each plant type are determined. It is clearly seen that the annual levelized. cost for additional power plants varies with the economic parameters. The results show that the economic parameters variation has to be taken into consideration in electricity generation planning. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: power generation; economic parameters; capacity expansion; Thermodynamics; Energy & Fuels; Mechanics